Efficacy of maternal B12 supplementation in vegetarian women for improving infant neurodevelopment: protocol for the MATCOBIND multicentre, double-blind, randomised controlled trial. Issue 5 (25th May 2020) - Nagpal, Jitender; Mathur, Manu Raj; Rawat, Swapnil; Nagrath, Deepti; Lee, Charlotte; Singhal, Atul; Heys, Michelle; Cortina Borja, Mario; Augustin, Katrin; Gautam, Jageshwor; Pant, Rajendra; Swabey, Laura; et al.
Abstract : Introduction: Vitamin B12 deficiency is widely prevalent across many low- and middle-income countries, especially where the diet is low in animal sources. While many observational studies show associations between B12 deficiency in pregnancy and infant cognitive function (including memory, language and motor skills), evidence from clinical trials is sparse and inconclusive. Methods and analysis: This double-blind, multicentre, randomised controlled trial will enrol 720 vegetarian pregnant women in their first trimester from antenatal clinics at two hospitals (one in India and one in Nepal). Eligible mothers who give written consent will be randomised to receive either 250 mcg methylcobalamin or 50 mcg (quasi control), from enrolment to 6 months post-partum, given as an oral daily capsule. All mothers and their infants will continue to receive standard clinical care. The primary trial outcome is the offspring's neurodevelopment status at 9 months of age, assessed using the Development Assessment Scale of Indian Infants. Secondary outcomes include the infant's biochemical B12 status at age 9 months and maternal biochemical B12 status in the first and third trimesters. Maternal biochemical B12 status will also be assessed in the first trimester. Modification of association by a priori identified factors will also be explored. Ethical considerations and dissemination: The study protocol has been approved by ethical committees at each study site (India and Nepal) and at University College London, UK. The study results will be disseminated to healthcare professionals and academics globally via conferences, presentations and publications. Researchers at each study site will share results with participants during their follow-up visits. Trial registration number CTRI/2018/07/015048 (Clinical Trial Registry of India); NCT04083560 (ClinicalTrials.gov)